2022
DOI: 10.1101/2022.11.02.514843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altering stimulus timing via fast rhythmic sensory stimulation induces STDP-like recall performance in human episodic memory

Abstract: Animal studies suggest that the strength of synaptic modification depends on spike timing between pre- and post-synaptic neurons on the order of tens of milliseconds, which is termed spike-timing-dependent plasticity (STDP). However, evidence for STDP in human episodic memory is lacking. We investigated this using rhythmic sensory stimulation to drive visual and auditory cortices at 37.5 Hz with four phase offsets. Visual relative to auditory cued recall accuracy was significantly enhanced in the 90 degree con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Finally, subthreshold synaptic inputs are a key substrate for synaptic plasticity. Indeed, two separate studies in mice and humans have recently suggested that 40 Hz stimulation can enhance synaptic plasticity [64,69].…”
Section: The Brain-wide Neuronal Response To Gamma Stimulationmentioning
confidence: 99%
“…Finally, subthreshold synaptic inputs are a key substrate for synaptic plasticity. Indeed, two separate studies in mice and humans have recently suggested that 40 Hz stimulation can enhance synaptic plasticity [64,69].…”
Section: The Brain-wide Neuronal Response To Gamma Stimulationmentioning
confidence: 99%
“…Later, 24 participants were cued with one of the sounds and recalled the paired video. The other 24 participants were cued with a video and asked to recall the paired sound 22 .…”
Section: Humans Show Neural Response To Gamma Sensory Stimulationmentioning
confidence: 99%
“…Later, 24 participants were cued with one of the sounds and recalled the paired video. The other 24 participants were cued with a video and asked to recall the paired sound 22 . The results ( Figure 1C-E ) not only show phase-locked responses in the hippocampus and prefrontal cortex (PFC) to the stimulation, but they also show that this response is modulated by memory success (i.e., stronger responses to remembered vs. forgotten trials) 22 .…”
Section: Hz Electrophysiological Response Throughout the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual sensory stimulation is a technique in which a stimulus's luminance oscillates over time and aims to modulate ongoing neural activity. While low-frequency sensory stimulation can modulate endogenous low-frequency oscillations 49 and enhance episodic memory formation 50 , and gamma-band sensory stimulation can induce gamma-band activity in the thalamus, visual cortex and hippocampus [51][52][53][54][55] , it remains unclear whether gamma-band sensory stimulation can enhance recall performance above and beyond what is observed when stimulation is not applied. Importantly, as sensory stimulation using fast gamma rhythms (>60Hz) involves flickering the stimuli at rates above the flicker fusion threshold, the flickers are imperceptible to the naked eye and, therefore, may provide an imperceptible intervention to enhance episodic memory.…”
Section: Introductionmentioning
confidence: 99%